Efektifitas Larvasida Nabati dalam Membunuh Larva Aedes Spp - Harun Alrasyid Adenan; Muhammad Irfa'i; Isnawati Isnawati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2018)
Effectiveness of Vegetable Larvacide in Killing Aedes Spp. Larvae. DHF (Dengue Haemorrhagic Fever) is caused by Aedes spp. vector. Controlling of this disease has used chemist or insecticide. The insecticide for killed larva Aedes spp. is abate. Using insecticide for a while can make vector has resistance. Base on the fact, we need subtances alternative of controlling which can degredable it’s from naturall like garlic (Allium sativum), papaya (Carica papaya) core and piper betle. This research aimed for efectivities of larvacide garlic, papaya core and betel vine. This research is a true experimental, used toxicity experiment standart. Result both LC99 and Toxid Unit (TU) of larvacide garlic is 7,7 gr/L and 26,88. Larvacide papaya core is 10,22 gr/L and 16,33. Larvacide vine betel is 74,4 gr/L and 2,65. Decided of larvacides which efectivest are compared TU value that higher. Based on TU values, larvacide which efectivest and can aplicate for killing larva is garlic. Larvacide of garlic can use in places that contain water which difficult to drained or washed.